The Mainstreaming of Pesantrens and Madrasahs in Indonesia - Jamhari, Jamhari (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2005)
The project of this article has focused on six strategic groups in pesantrens and madrasahs. These are: 1)Kyai (male religious leaders) and Nyai (female religious leaders) of pesantren salaf; 2) Kyai and Nyai of pesantren khalaf; 3) key community leaders; 4) principals ofmadrasah aliyahmadrasah aliyah; and 6) student leaders of madrasah aliyah.DOI: 10.15408/sdi.v12i2.593